2006
DOI: 10.1086/499497
|View full text |Cite
|
Sign up to set email alerts
|

Optical Spectroscopy of a Flare on Barnard’s Star

Abstract: ABSTRACT. We present optical spectra of a flare on Barnard's star. Several photospheric and chromospheric species were enhanced by the flare heating. An analysis of the Balmer lines shows that their shapes are best explained by Stark broadening rather than chromospheric mass motions. We estimate the temperature of the flaring region in the lower atmosphere to be ≥8000 K and the electron density to be ∼10 14 cm Ϫ3 , similar to values observed in other dM flares. Because Barnard's star is considered to be one of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 42 publications
(69 reference statements)
3
62
0
Order By: Relevance
“…4.5). Similar emission lines were observed during a flare of the M4V dwarf GJ699 by Paulson et al (2006).…”
Section: Ut Datesupporting
confidence: 76%
“…4.5). Similar emission lines were observed during a flare of the M4V dwarf GJ699 by Paulson et al (2006).…”
Section: Ut Datesupporting
confidence: 76%
“…For even higher members of the Balmer series, it is not clear whether their broad line components start to merge. Moreover, Paulson et al (2006) also found less broadening in higher Balmer lines and gave NLTE effects as a possible reason, which affect low order lines most.…”
Section: Stark Broadening Versus Turbulent Broadeningmentioning
confidence: 87%
“…They can be blue-or (more often) red-shifted, and are often ascribed to a moving turbulent plasma component. Broadening, especially of hydrogen lines, may also be caused by the Stark effect; for a flare on Barnard's star, Paulson et al (2006) attributed a symmetric line broadening to the Stark effect. Also, for the Sun Johns- Krull et al (1997) found evidence of Stark broadening in higher order Balmer lines during a strong flare.…”
Section: Broad Line Componentsmentioning
confidence: 99%
“…Stark broadening is thought to be an important symmetric broadening mechanism of the hydrogen Balmer lines during solar and stellar flares (Svestka, 1963;Worden et al, 1984;Hawley and Pettersen, 1991;Johns-Krull et al, 1997;Paulson et al, 2006;Allred et al, 2006), in addition to possible turbulent (Eason et al, 1992;Doyle et al, 1988) and thermal contributions. The linear (first order) Stark effect is the splitting of the degenerate orbital angular momentum (l) states of each principal quantum state (n) of hydrogen, due to a net electric microfield from the surrounding distribution of charges.…”
Section: Stark Broadening At the Balmer Edgementioning
confidence: 99%